Essential oils with tick activity against Rhipicephalus (Boophilus) microplus and Rhipicephalus sanguineus: a review: Aceites esenciales con actividad garrapaticida contra Rhipicephalus (Boophilus) microplus y Rhipicephalus sanguineus: una revisión (Research, Society and Development, 2022)
Ticks are ectoparasitic arthropods, hematophagous that parasitize several vertebrate hosts, and are found both in urban and rural areas, being Rhipicephalus sanguineus the main species found in dogs and Rhipicephalus (Boophilus) microplus in cattle. The use and search for natural products, especially vegetables, to control these parasites is currently intensifying because being safer and less aggressive to man, animals and the environment. Thus, the aim of this study was to survey the main essential oils with tick activity and describe the main chemical constituents involved in this activity. Therefore, a systematic review of articles was carried out using the databases of Google School, SciELO and CAPES Periodicals, between the years 2008 and 2020. The tick activity of essential oils was observed in 28 plant species distributed in 13 botanical families, being 13 tested against R. (Boophilus) microplus and 05 against R. sanguineus. Thirteen major substances were found repeated in two or more species, with limonene (06 spp.), (E) -ß-caryophyllene (05 spp.) and α-pinene (05 spp.) being the most cited compounds. The data from the present study can serve as a basis for future research, for the selection of plant species and potential substances for tick tests.